Social Responsibility In Islam: A Study in Textual Roots and Contemporary Linguistic Manifestations/ المسؤولية الاجتماعية في الإسلام دراسة في الجذور النصية والتجليات اللغوية المعاصرة - Faisal Mohammad Mohammad Hasan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research provides a comprehensive study of Islamic social responsibility through textual and linguistic analysis, addressing its contemporary applications. The study's objective is to investigate the conceptual foundations of social responsibility in Islamic primary sources, examine its linguistic representations, and analyze the challenges of its modern implementation. The methodology combines inductive analysis of religious texts with linguistic examination and contemporary case studies. Key findings demonstrate that the linguistic structure of Islamic texts utilizes precise terminology and rhetorical methods that effectively reinforce social responsibility. Empirical evidence indicates that societies that implement Islamic social principles exhibit significantly higher rates of family stability and psychological well-being than contemporary alternatives. The study concludes that the Islamic approach to social responsibility offers a comprehensive framework for social cohesion. Primary recommendations include integrating Islamic social concepts into educational systems, developing flexible legislative frameworks for family law, and utilizing digital platforms for community engagement.